Approach of Ebû Hanifa on The Dıvıne Attributes - SARIBULAK, Zekerya (Scientific Journal of Faculty of Theology, 2018)
Sıfat matter is one of the first subject which Kalamists argue about.At the same time it’s an argue that which creates Islamic Kalam.There had been a lot of issues on this subject.But there is no consensus that when or by whom it was started.Among this diffirent views,some called “Muattıla” because of their views about Sıfat.Some other called “Musebbihe” because of their metaphoric views to Allah linked to humankind.But Ehl-i Sunnet sect has followed a common way between the two sides.When it is looked to boks, which are believed to belong to Ebu Hanife,it is understood that , he followed a common way either. As a result,in this work,it will be tried to understand both Ebu Hanife’s thoughts about Sıfat and Ehl-i Sunnet’s effect on Sıfat view.